Accounting Recording System Design At Bentely Tyre Repair Shop - Olga Yolenta; Sari Dewi (ConCEPt - Conference on Community Engagement Project, 2023)
There are no financial recording at Bentley Tyre Repair Shop. The Bentley repair shop also does not provide receipts for sales or revenue. To solve the problem, a computer based accounting system was created. The system was created using Microsoft access which produces financial reports in the form of inventory cards, profit or loss reports, purchase reports, income reports, sales reports, and statements of financial reports. The output would guide the repair shop in knowing their profit and inventory. System design is carried out according to the needs and requests of MSME owners, so that the system can be run easily and produces accurate information.